(untitled) (The Strategic Review for Southern Africa, 2020)
The paper analyses South Africa-China relations emphasising how changing identities of the two countries since the 1940s define their outlook on critical issues such as human rights and democracy. Sino-South African relations are divided into three epochs. The first covers the Mao era; the second traverses the post-Mao era and the subsequent economic and modernization reforms up to the end of the Cold War; the third and current epoch roughly starts in 1994, after the establishment of democracy in South Africa. Constructivism is used as the theoretical framework to interpret the evolving South Africa-China relationship. This study adopted a qualitative approach. The outcome of the study is that changes in identity of these two nations have shaped their national interests. Thus, when countries share identities and interests - be they good or controversial – stable cooperation is possible among them. In this vein, constructivism concedes that shared or differing identities and interests among states can produce either cooperative or conflictual relations. This distinguishes constructivism from idealism, a theory under which it has often been subsumed.